Task analysis of laparoscopic camera control schemes†. Issue 4 (9th December 2015) - Ellis, R. Darin; Munaco, Anthony J.; Reisner, Luke A.; Klein, Michael D.; Composto, Anthony M.; Pandya, Abhilash K.; King, Brady W.
Abstract: Background: Minimally invasive surgeries rely on laparoscopic camera views to guide the procedure. Traditionally, an expert surgical assistant operates the camera. In some cases, a robotic system is used to help position the camera, but the surgeon is required to direct all movements of the system. Some prior research has focused on developing automated robotic camera control systems, but that work has been limited to rudimentary control schemes due to a lack of understanding of how the camera should be moved for different surgical tasks. Methods: This research used task analysis with a sample of eight expert surgeons to discover and document several salient methods of camera control and their related task contexts. Results: Desired camera placements and behaviours were established for two common surgical subtasks (suturing and knot tying). Conclusion: The results can be used to develop better robotic control algorithms that will be more responsive to surgeons' needs. Copyright © 2015 John Wiley & Sons, Ltd.